Ecological Enhancement of Agaricus bisporus L. Mushrooms' Vitamin Content Using Carbon Nanotubes, Magnetic Iron Nanoparticles, and Biostimulants - Algarawi, Mustafa; Al-Juthery, Hayyawi; Chechan, Rukaibaa (Research in Ecology, 2025)
The edible mushroom Agaricus bisporus L. plays a crucial ecological role in nutrient cycling and organic matter decomposition, alongside its increasing importance in the food and nutrition industry. This study explored ecological interventions to enhance the mushroom's vitamin content by enriching its cultivation substrate with nanomaterials and biostimulatory agents. The experiment was conducted within the mushroom production project at Al-Qadisiyah Governorate, Iraq. The compost-based medium was amended with magnetic iron nanoparticles (N-FeO), carbon nanotube (CNT) suspensions, EM biofertilizer, and Atonik growth stimulant. Their ecological impact on the enrichment of fat-soluble (A, D, E) and water-soluble (B2, B3, B5, B6) vitamins in mushrooms was assessed. The study employed a Completely Randomized Design (CRD) with three replicates. Results revealed that the synergistic application of these eco-friendly treatments significantly enhanced the vitamin profiles of A. bisporus. The highest concentrations of vitamins B2 and B5 (5.16 and 17.70 mg kg⁻¹, respectively) and vitamin A (6.87 IU ml⁻¹) were recorded under the combined quadruple treatment. Additionally, the triple treatment (N-FeO + EM + Atonik) notably increased levels of vitamins B2 (4.47 mg kg⁻¹), B6 (25.66 mg kg⁻¹), D (34.76 mg kg⁻¹), and vitamin A (6.87 IU ml⁻¹). Dual treatments (EM + Atonik) also significantly improved vitamin B2 (4.54 mg kg⁻¹) and vitamin E (3.30 mg kg⁻¹) contents. These findings demonstrate that integrating nanomaterials and biostimulants can serve as an ecological strategy to improve the nutritional quality of mushrooms while promoting sustainable agricultural practices.